Greek Decision-Making and the Battle of the Sakarya River, 1921: Towards a New Assessment? - Sayen, George (Journal Of Military History and Defence Studies, 2022)
The article seeks to reassess certain key decisions by the leadership of the Greek Field Army of Asia Minor (FAAM) in connection with the battle of the Sakarya River (23 August to 14 September 1921), at which the FAAM reached the high water mark of its campaign against the Turkish Nationalist forces during the Greco-Turkish War of 1919 – 1922. The article focuses on the Greek decisions (i) to exploit their victory at Eskişehir in July 1921 by crossing the Sakarya river and attempting to capture the Nationalist capital of Ankara, (ii) to attack the Nationalist forces arrayed behind the Sakarya river by way of an envelopment of their southern flank rather than a direct assault and (iii) to abandon the offensive and withdraw on 11-13 September 1921. The article argues that the historiography of the campaign, particularly in English, has tended to be overly critical of the first of the above decisions and insufficiently critical of the latter two. It concludes that (i) there were compelling reasons for the FAAM to make a determined attempt to capture Ankara despite the challenges and risks of doing so, (ii) the plan of battle was overly complex and risky from a tactical and a logistical standpoint whilst a direct assault across the river might have been more effective and involved less risk, and (iii) the withdrawal may have been premature. While it has been argued that the Sakarya river campaign is a classic illustration of Clausewitz’s concept of a ‘culminating point’, at which an offensive pushed too far yields the advantage to the defender, the article argues that it has just as much to teach about Clausewitz’s countervailing principle of ‘continuity’, which holds that an insufficiently aggressive follow up of an initial victory can lead to unnecessary defeat.